Does Google serve as a model for using place names? - Gercsák, Gábor; Mikesy, Gábor (Acta geographica Slovenica, 2017)
This paper examines the reliability of geographical names published on various internet platforms and seeks to improve the place-name content of internet maps. Hungarian examples of incorrect place names from various online maps draw attention to the need for cooperation between those that provide internet maps or map-based applications and relevant national or professional institutions.